2005
DOI: 10.1128/jb.187.12.4005-4014.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Small Untranslated RNA RyhB and Its Regulon inVibrio cholerae

Abstract: Numerous small untranslated RNAs (sRNAs) have been identified in Escherichia coli in recent years, and their roles are gradually being defined. However, few of these sRNAs appear to be conserved in Vibrio cholerae, and both identification and characterization of sRNAs in V. cholerae remain at a preliminary stage. We have characterized one of the few sRNAs conserved between E. coli and V. cholerae: RyhB. Sequence conservation is limited to the central region of the gene, and RyhB in V. cholerae is significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 43 publications
8
116
0
1
Order By: Relevance
“…However, the interaction between RyhB and sodB mRNA is mediated through other regions of the sRNAs in the two organisms (Davis et al 2005), suggesting that the different variants of Hfq might have different binding preferences, which might have supported the regulatory interactions for these sRNAs and, consequently, their maintenance inside the Enterobacteriales order.…”
Section: Discussionmentioning
confidence: 99%
“…However, the interaction between RyhB and sodB mRNA is mediated through other regions of the sRNAs in the two organisms (Davis et al 2005), suggesting that the different variants of Hfq might have different binding preferences, which might have supported the regulatory interactions for these sRNAs and, consequently, their maintenance inside the Enterobacteriales order.…”
Section: Discussionmentioning
confidence: 99%
“…In V. cholerae, RyhB modulates the expression of several genes controlling motility, chemotaxis, and biofilm formation. However, a ⌬ryhB mutant is still able to infect mice (24,25). Production of capsular polysaccharide and iron acquisition systems, two factors required for survival within the human host, are regulated by RyhB in K. pneumoniae (26).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, RyhB plays an essential role in bacteria that require adaptation to iron starvation. Moreover, this sRNA also contributes to many pathogenicity determinants, such as acid resistance in Shigella flexneri (21); eukaryotic cell invasion and cell-to-cell spread in Shigella dysenteriae (22,23); motility, chemotaxis, and biofilm formation in Vibrio cholerae (24,25); biosynthesis of capsular polysaccharide and iron acquisition in Klebsiella pneumoniae (26); and oxidative stress resistance, survival inside human macrophages, and iron acquisition in Salmonella enterica serovar Typhi (27).…”
mentioning
confidence: 99%
“…Analysis of the RyhB regulon in V. cholerae showed that RyhB influenced the synthesis of superoxide dismutase, TCA cycle enzymes, and proteins containing heme or iron-sulfur clusters (21,236). However, V. cholerae RyhB is considerably larger than its E. coli homolog (Ͼ200 nucleotides, compared to 90 for E. coli) and has a larger regulon, influencing the expression of genes involved in motility, chemotaxis, and biofilm formation.…”
Section: Iron and Regulatory Rnasmentioning
confidence: 99%